2018
DOI: 10.1007/s00540-018-2495-7
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Japanese translation of the DN4 Diagnostic Questionnaire in patients with neuropathic pain

Abstract: The Japanese version of the DN4 was found to be a helpful tool for discriminating between neuropathic and non-neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Items from #1 to #7 of the DN4 questionnaire are answered by interviewing patients, and items from #8 to #10 require examination of patients. DN4 score is the total of these 10 items existing in each patient, and the cut-off value for a diagnosis of neuropathic pain is a score of 4/10 2,3. The reliability, validity, and specificity of the Japanese version of the DN4 diagnostic questionnaire were confirmed in our previous study 3…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…Items from #1 to #7 of the DN4 questionnaire are answered by interviewing patients, and items from #8 to #10 require examination of patients. DN4 score is the total of these 10 items existing in each patient, and the cut-off value for a diagnosis of neuropathic pain is a score of 4/10 2,3. The reliability, validity, and specificity of the Japanese version of the DN4 diagnostic questionnaire were confirmed in our previous study 3…”
Section: Methodsmentioning
confidence: 69%
“…Neuropathic pain is caused by a lesion or disease of the somatosensory nervous system. Although whether neuropathic pain can or cannot describe some of the underlying mechanisms of painful cranial neuropathies and other facial pains is unresolved, recent reports, using the Douleur Neuropathique 4 (DN4) questionnaire for screening neuropathic pain,2,3 have shown that 69.2% of the patients with trigeminal neuralgia present with neuropathic pain4 and 31% of the patients with burning mouth syndrome present with neuropathic pain 5…”
Section: Introductionmentioning
confidence: 99%
“…We used the DN4 questionnaire to discriminate neuropathic pain from other pain states [7,8]. The DN4 questionnaire evaluates 10 items: characteristics of pain (burning (1), painful cold (2), electric shocks (3)), symptoms in the region of pain (tingling (4), pins and needles (5), numbness (6), itching (7)), localized pain (hypoesthesia to touch (8), hypoesthesia to pricking (9)) and pain caused or increased by brushing in the painful area (10).…”
Section: Pain Assessmentsmentioning
confidence: 99%
“…Items #1 to #7 of the DN4 questionnaire are answered by interviewing patients, and items #8 to #10 require examination of patients. DN4 score is a total count of these 10 items for each patient, and the cut-off value for the diagnosis of neuropathic pain is a score of 4/10 [7,8]. DN4 scores were graded as three levels, i.e.…”
Section: Pain Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation